Forest fire causes and motivations in the Southern and South-Eastern Europe through experts' perception and applications to current policies - Tedim, Fantina (2022)
Forest fires causes and motivations are poorly understood in southern and south-eastern Europe. This research aims to identify how experts perceive the different causes of forest fires as defined in the classification proposed by the European Commission in 2013. A panel of experts (N = 271) was gathered from the EU Southern Member States (France, Greece, Italy, Portugal, and Spain) and from Central (Switzerland) and south-eastern Europe (Croatia, Serbia, Bosnia and Herzegovina, Republic of North Macedonia, and Turkey). Experts were asked to answer a questionnaire to score the importance of the 29 fire causes using a five point (1-5) Likert Scale. Agricultural burnings received the highest score, followed by Deliberate fire for profit, and Vegetation management. Most of the events stem from Negligence, whereas malicious fire setting is arguably overestimated although there are differences among the countries. This research demonstrates the importance of different techniques to enhance the knowledge of the causes of the complex anthropogenic phenomenon of forest fire occurrence